Exploring the significance of toponyms in the university linguistics curriculum : insights from Kibera in Kenya and Sabalibougou in Mali - Otundo, Billian; Doumbia, Lamine (Curriculum Perspectives, 2023)
Africa’s linguistic diversity and cultural richness make it an ideal setting for incorporating case studies of toponyms (place names) into the university linguistics curriculum. By examining the toponyms of Kibera slum areas in Kenya and those of the people of Sabalibougou in Southern Mali, this article explores the various ways that toponyms can be used to enhance the understanding of African languages and cultures. Based on the premise that toponyms communicate knowledge about the natural world, peoples’ experiences, indigenous and local languages, and history, the two case studies of this article highlight the following factors as reasons why toponyms should be studied and incorporated into the university’s linguistics curricula: (i) They reveal the interplay between history, socio-political manifestations, and language; (ii) provide awareness of the role of geography on language, language contact, and language endangerment; (iii) facilitate the relationship between language and culture; and (iv) allow practising orthography, phonetic transcription, and morphosemantics of African languages. Hence, incorporating toponym case studies, like those provided in this study, into the linguistics curriculum can enable students to better comprehend and appreciate Africa’s linguistic diversity and cultural richness, ultimately contributing to the decolonisation of education in Africa.
Keywords: Toponyms; Endogenous knowledge; University education; Linguistics curriculum; Mali; Kenya